Non-Formal Primary Education programme of BRAC for out-of school children - BRAC (© BRAC, 2016)
1. Introduction 2. Goal of NFPE 3. Programme objective 4. Programme activities 5. Teaching and supervision 6. Up-to-date achievement 7. Conclusion